Making health choices; Part 1. Advance Care planning in aged care project. Setting the scene. Issue 1 (1st June 2011) - Jackson, L; Sjanta, R; Fullam, R; Silvester, W
Abstract : Introduction: The (2009) Australian National Health & Hospital Reform Commission Report highlighted the need for advance care planning (ACP) for older persons in residential aged care facilities (RACFs). Using knowledge gained from a previous RACF Project Implementation in 2004-5, Respecting Patient Choices has developed a sustainability based model for the effective training of residential aged care service staff to deliver ACP to their residents. This presentation will provide a unique insight into the complexities of ACP implementation within Australian residential aged care. Project methods: 19 individual RACFs, representing 12 Aged Care organisations were selected from regional and metropolitan areas of Victoria. Three full-day workshops were delivered over a 6 month period, with RACFs expected to complete sustainability oriented tasks in between each workshop in order to meet the project deliverables. As part of the project an aged care specific ACP document was developed by an expert working party. Pre-implementation over-view: A number of contextual factors have impacted the present project including; Australian geography, RACF funding issues, and provision of medical support to RACF residents. Results: from a pre-implementation policy and practice survey demonstrated a wide variation of the quality of existing ACP knowledge and practices. An audit of pre-existing ACP documents revealed that all documents were missing key elements of a best practice ACP document. 11 of the 12 organisations in the project have adopted the specially developed document.